Effects of Different Priming Treatments on The Germination and Growth of Okra (Abelmoschus esculentus L.) - Alam, Md. Mahbub; Khan, Mujibur Rahman; Hossain, Muhammad Sajjad; Sultana, Mst. Sadia; Anjum, Md. Tanvir (Department of Agronomy and Horticulture, IPB University, 2024)
The study was designed to overcome the low germination of okra seed and to assess the effects of different seed priming treatments on okra (Abelmoschus esculentus) seedlings, which were encompassed nine treatments: control, hydro priming, SMP-sand metrix priming, H2SO4 - 40%, H2O2 - 2%, NaCl - 3%, KCl - 3%, CaCl2 - 3%, and KI - 1%. A randomized complete block design was used with three replications. Germination percentages, germination speed index (GSI), seedling vigor index (SVI), and relative growth rate (RGR) were measured. The highest germination percentage (89.77%) and GSI (9.6) were observed with (H2O2 - 2%). T3 (H2SO4 - 40%) exhibited the highest SVI (0.7), indicating robust seedling health. Additionally, H2O2 - 2%. demonstrated the longest root and shoot length (11.7 cm and 14.2 cm, respectively) and highest seedling fresh weight (0.87 g). Treatment with H2SO4 - 40% displayed the highest dry weight (0.18 g). Notably, H2O2 - 2% treatment significantly enhanced germination and growth compared to the control. These findings underscore the potential of seed priming, particularly H2O2 - 2%, in enhancing okra seedling growth and development, offering valuable implications for crop productivity and establishment.